IMPORTANCE OF DIGITAL TRANSFORMATION IN SUSTAINABLE ECONOMIC DEVELOPMENT AND INTEGRATION OF ENVIRONMENTAL, SOCIAL AND GOVERNANCE WITH INVESTMENTS (Marketing Journal, 2025)
This article examines the role of digital transformation in sustainable economic development and its integration with ESG (Environmental, Social, Governance) investments. It highlights the significance of digital technologies, including IoT, Big Data, artificial intelligence, and blockchain, in implementing ESG principles. The paper discusses the growth trends of ESG investments in global financial markets and strategic initiatives in Uzbekistan related to digital transformation and the green economy. Based on international experience, the interconnection between ESG and digital transformation is analyzed, emphasizing their importance for the sustainable development of Uzbekistanʼs economy.
Keywords: digital transformation; ESG investments; Sustainable development; IoT (Internet of Things); Big Data; Artificial intelligence (AI); Blockchain technology